PENGUASAAN MATERI KAPITA SELEKTA FISIKA SEKOLAH II MAHASISWA PENDIDIKAN FISIKA FKIP UNRI MELALUI PENERAPAN MODEL PEMBELAJARAN SEARCH SOLVE CREATE SHARE - Azizahwati Azizahwati (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2008)
The purpose of this research was to describe the student physic approachment trough Search Solve CreateShare of model learning on the major of Kapita Selekta Fisika Sekolah II . The subject of this research was32 students of Physic Department of FKIP UNRI on 2007-2008 academic’s year. The Instrument ofcollecting data was achivment test. The describe analysis showed that the average of relatives frequency ofscore was 52,2 %.Key words: approach of materi, SSCS